The effect of IGF-1 plasma concentration on COVID-19 severity. (March 2022) - Hazrati, Ebrahim; Gholami, Mohammad; Farahani, Ramin Hamidi; Ghorban, Khodayar; Ghayomzadeh, Morteza; Rouzbahani, Negin Hosseini
Abstract: Background: The severity and fatality of Coronavirus disease 2019 (COVID-19) infection are not the same in the infected population. The host immune response and Immune-stimulating factors appear to play a role in COVID-19 infection outcome. insulin-like growth factor-1 (IGF-1) affects the immune system by controlling the endocrine system. Recently, the effect of IGF-1 levels on COVID-19 prognosis has been considered. Objective: To investigate the difference between circulating IGF-1 and inflammatory cytokines concentration among COVID-19 patients, infected patients admitted to the Intensive Care Unit (ICU) (n = 40; 35 ± 5 y) and patients with mild cases of COVID-19 (n = 40; 35 ± 5 y) were screened prior to participation in the study. There was no significant difference between the groups in terms of gender and preexisting inflammatory state. Collected samples were evaluated by ELISA for IGF-1 and IL-6. Results: The study outcomes included a significant decrease in IGF-1 and an increase in IL-6 serum concentration, as an inflammatory marker, for infected patients admitted to the Intensive Care Unit (ICU) (P ≤ 0.001). Finally, there was a significant increase in the IGF-1 and a decrease in the IL-6 serum concentration of hospitalized patients. Discussion: it appears that inflammatory cytokines (IL-6) serum concentration in the severe form of corona virus-based infections causes reduced defenses because of suppressed IGF-1. Conclusions: Our findings show that lower IGF-1 concentrations are associated with a Severe form of COVID-19 disease. It seems, IGF-1 supplementation or anti-inflammatory treatment rescued the severe form of COVID-19 infection. Further studies are required to determine how to design COVID-19 therapeutic strategies targeting the IGF-1 pathway. Highlights: Plasma insulin-like growth factor-1 (IGF-1) concentration effects on immune responses. Plasma concentration of IGF-1 is significantly different between mild and severe cases of COVID-19. There is a significant negative association between plasma levels of IGF-1 and IL-6 in COVID-19 patients.